Gurkha the illustrated history - Harclerode, Peter 1947-; Reynolds, David (Sutton Publishing Limited, 2003)
Following a brief history of the Gurkhas in the 19th century, the author examines their role in both World Wars and their extensive post-war active service in Malaya, Brunei and the Falklands and their more recent contributions in Bosnia, Kosovo, East Timor and Sierra Leone